Computed Tomography (CT) of bowel and mesenteric injury in blunt abdominal trauma: a pictorial essay - Hassan, Radhiana; Abd. Aziz, Azian; Che Mohamed, Siti Kamariah (Malaysian Medical Associations, 2012)
Computed tomography (CT) is currently the diagnostic modality of choice in the evaluation of clinically stable patients with blunt abdominal trauma, including the assessment of blunt bowel and mesenteric injuries. CT signs of bowel and/or mesenteric injuries are bowel wall defect, free air, oral contrast material extravasation, extravasation of contrast material from mesenteric vessels, mesenteric vascular beading, abrupt termination of mesenteric vessels, focal bowel wall thickening, mesenteric fat stranding, mesenteric haematoma and intraperitoneal or retroperitoneal fluid. This pictorial essay illustrates CT features of bowel and/or mesenteric injuries in patients with blunt abdominal trauma. Pitfalls in interpretation of images are emphasized in proven cases.